2000
DOI: 10.1161/01.atv.20.3.846
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis Progression in LDL Receptor–Deficient and Apolipoprotein E–Deficient Mice Is Independent of Genetic Alterations in Plasminogen Activator Inhibitor-1

Abstract: Abstract-Impaired fibrinolysis has been linked to atherosclerosis in a number of experimental and clinical studies.Plasminogen activator inhibitor type 1 (PAI-1) is the primary inhibitor of plasminogen activation and has been proposed to promote atherosclerosis by facilitating fibrin deposition within developing lesions. We examined the contribution of PAI-1 to disease progression in 2 established mouse models of atherosclerosis. Mice lacking apolipoprotein E (apoEϪ/Ϫ) and mice lacking the low density lipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 49 publications
1
65
2
Order By: Relevance
“…Genotyping for FVL and ApoE was performed by polymerase chain reaction (PCR) analysis of tail DNA with the primers previously described. 13,14 After weaning, at 3 weeks of age, mice were fed standard chow (laboratory rodent diet No. 5001, TestDiet).…”
Section: Micementioning
confidence: 99%
“…Genotyping for FVL and ApoE was performed by polymerase chain reaction (PCR) analysis of tail DNA with the primers previously described. 13,14 After weaning, at 3 weeks of age, mice were fed standard chow (laboratory rodent diet No. 5001, TestDiet).…”
Section: Micementioning
confidence: 99%
“…Male mice of 8 weeks were fed a Western type diet containing 15% (w/w) cacoa butter and 0.25% (w/w) cholesterol (diet W, Hope Farms, Woerden, The Netherlands) for 6 weeks, which leads to appreciable atherosclerosis (22)(23)(24). Animals were anesthetized using isoflurane, and in situ fixation was performed via the left ventricle of the heart using phosphate-buffered formalin (4%, v/v).…”
Section: Atherosclerosismentioning
confidence: 99%
“…Comparison of the effects of Serp-1 to that of PAI-1 may thus hold a key to elucidation of the actual mechanism by which Serp-1 exerts its atheroprotective effect. Unfortunately, conflicting data on PAI-1 2,12,13 emphasize that the effects of modulation of serine protease activity are intricately dependent on the local protease milieu and the disease progression and leave unanswered to what extent antiinflammatory effects of Serp-1 may contribute to its beneficial effect as well. Other studies on the role of tPA and uPA in atherogenesis have shown that overexpression of uPA in carotid arteries in rabbits results in an acceleration of plaque growth, although no difference in plaque morphology was observed.…”
Section: Discussionmentioning
confidence: 99%
“…11 The precise relevance of these inhibitors to atherosclerosis is largely unclear. Thus, some researchers have found the serpin plasminogen activator inhibitor-1 (PAI-1) to have no effect on de novo atherogenesis in hypercholesterolemic mice, 12 whereas others have demonstrated PAI-1 deficiency to be atheroprotective in early atherosclerosis 2 and to accelerate plaque progression in advanced atherosclerosis. 13 Its effect in restenosis appears to be more clear-cut, as studies have demonstrated an exacerbating role for PAI-1 in neointima formation by promoting smooth muscle cell migration and proliferation.…”
mentioning
confidence: 99%